Increasing Serum Transaminase and The Relation with The Serum Concentration of Isoniazid and Rifampicin of Tuberculosis Patients which Given Antituberculosis Fixed Dose Combination in Yogyakarta - Ratih Puspita Febrinasari; Erna Kristin; Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACT Tuberculosis is still a major health problem in Indonesia. Isoniazid and rifampicin are major antituberculosis drugs. These two drugs have been known to cause hepatotoxicity which is characterized by an increase of serum transaminase concentration. Previous study proved the increase of hepatotoxicity due to isoniazid and rifampicin but did not explain about the correlation with the drugs concentration. The aim of this study is to know the relation between increasing serum transaminase and the serum concentration of  isoniazid and rifampicin of tuberculosis patients which given antituberculosis fixed dose combination in Yogyakarta. We carried out a cross sectional study involving 31 TB patients who received antituberculosis fixed dose combination containing isoniazid and rifampicin. Serum transaminase was measured with an automatic chemical analyzer. Isoniazid and rifampicin concentration was measured by using HPLC. We used t- test, Mann Whitney, Fisher and Spearman to analyze the data. There is no correlation between mean isoniazid concentration with high (7,07±6,24mg/ml) and normal ALT (2,42±0,26mg/ml)  (p>0,05). There is no correlation between mean isoniazid concentration with high (5,03+4,14 mg/ml) and normal AST (p>0,05). There is no correlation between mean rifampicin concentration with high (10,67+3,76 mg/ml) and normal ALT (3,66+0,30 mg/ml) (p>0,05). There is no correlation between mean rifampicin concentration with high (8,52+3,06 mg/ml) and normal AST (3,64+0,32 mg/ml) (p>0,05). Mean of rifampicin concentration in this study are low (4, 12+0,46 mg/ml). So the conclusion that there are no correlation between isoniazid serum concentration with an increase of serum transaminase and no correlation between rifampicin serum concentration with an increase of serum transaminase.